Peran Guru dalam Perkembangan Emosi Anak di Madrasah Ibtidaiyah - Rohmtul Ummah, Fina; Usriyah, Lailatul; Mu’alimin, Mu’alimin (Mulya Literasi Publishing, 2024)
The role of teachers in the development process is as important as the role of parents. Because development is systematic, progressive, and continuous. This study aims to determine how a teacher plays a significant role in the development of children in a madrasah. The method used in this study is a qualitative method. The results of the study indicate that teachers have a role in the emotional development of children while at school. Good development can be done by teachers in various ways such as monitoring what children do at school, building patterns of interaction and communication by being a good listener and building children's self-confidence at school, so that children are able to recognize themselves so that emotional development is optimal, finally by providing an understanding and explanation of what emotions are like and how to control them.